2003
DOI: 10.1007/s00216-003-2056-1
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of phytate ion in aqueous solution. Alkali metal complex formation in different ionic media

Abstract: The acid-base properties of phytic acid [ myo-inositol 1,2,3,4,5,6-hexakis(dihydrogen phosphate)] (H(12)Phy; Phy(12-)=phytate anion) were studied in aqueous solution by potentiometric measurements ([H+]-glass electrode) in lithium and potassium chloride aqueous media at different ionic strengths (0< I mol L(-1)< or =3) and at t=25 degrees C. The protonation of phytate proved strongly dependent on both ionic medium and ionic strength. The protonation constants obtained in alkali metal chlorides are considerably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 26 publications
6
58
0
Order By: Relevance
“…The solution of this complex task was found in the interaction between phytate and metallic ions and formation of a relatively strong complexes of the alkaline cations with phytates. 14,[24][25][26] As mentioned above sodium ions significantly increase acidity of phytate due to complexation (Fig. 2, curve a), but at this low concentration of titrant (low ionic strength, I), complete deprotonation to its final 12 th step does not occur.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The solution of this complex task was found in the interaction between phytate and metallic ions and formation of a relatively strong complexes of the alkaline cations with phytates. 14,[24][25][26] As mentioned above sodium ions significantly increase acidity of phytate due to complexation (Fig. 2, curve a), but at this low concentration of titrant (low ionic strength, I), complete deprotonation to its final 12 th step does not occur.…”
Section: Resultsmentioning
confidence: 66%
“…This effect is known well and is due to the complexation of Na + ions with phytate as phytic acid obtains an enhanced acidic character in the presence of alkali ions due to exchange of protons with Na + ions. 14,[24][25][26] However, in both cases only two EPs (EP 1 at pH 5.3 and EP 2 at pH 8.5-9.5) can be determined unambiguously. Further from the course of the titration curves is evident that phytic acid contains three categories of protons.…”
Section: Resultsmentioning
confidence: 98%
“…In this study, we observed that phytate forms fairly strong mixed (proton-amine) complexes, in particular when the charges of reactants involved in the formation equilibrium are quite high. In this order, here we investigated the interactions of phytate with an high molecular weight polyammonium cation (MW = 750 kDa), such as BPEI; the interactions were studied at low ionic strength values and without addition of supporting electrolyte, owing to the strong interference that phytate anion may undergo with alkali and alkaline earth metal cations [43,44]. Table 3 reports the overall complex formation constants obtained [equation (1)], whilst the equilibrium constants, according to the reaction (2), are reported in Table 4.…”
Section: Phy-bpei Speciesmentioning
confidence: 99%
“…In considering these formation constants and formation percentages, one must take into account that they were obtained in absence of an interacting supporting electrolyte such as NaCl, which is present in all natural and biological fluids. This is particularly important if we take into account that phytate forms stable complexes with alkali metals [28,43], and this interaction may change significantly the speciation of the system. The interaction of a polyammonium cation with phytate is dependent on the M A N U S C R I P T…”
Section: Phy-bpei Speciesmentioning
confidence: 99%
“…In fact, in our previous papers we thoroughly described the peculiarities of this molecule from a chemical, biological and environmental point of view, and we stressed several times that, despite the huge number of literature on phytate and its derivatives [see, for example, references in previous contributions [1][2][3][4][5][6][7][8][9] and in reviews [10][11][12][13] ], few quantitative data are presented on the modeling of their thermodynamic behavior in aqueous media. In this light, in our latest works we paid particular attention to the phytate speciation study in presence of heavy metal and organometal cations, such as mercury(II), 7 cadmium(II), 9 and dimethyltin(IV) cations.…”
Section: Introductionmentioning
confidence: 99%